Integrasi Nilai-Nilai Kewirausahaan Global pada Sistem Manajemen Bisnis Modern - Toyyibatul Mukminatus Sukriyah; Misbahul Arifin; Ramzatul Widad Rizqiyani; Ahmad Miftahuddin; Abdullah (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to examine the processes and implications of integrating global entrepreneurial values into a modern business management system at MTs Sunan Ampel as an Islamic educational institution responsive to global dynamics. Employing a qualitative approach with a case study design, the research explores in depth how global entrepreneurial values are embedded within institutional policies, leadership practices, organizational culture, and learning processes. Data were collected through observations, in-depth interviews, and document analysis involving the principal, vice principal for curriculum, teachers, and students. The data were analyzed through systematic stages of data reduction, data display, and verification, utilizing content analysis, discourse analysis, and interpretative analysis. The findings indicate that global entrepreneurial values such as innovation, adaptability, ethical leadership, sustainability, collaboration, and risk-taking have been systematically integrated into the school’s management framework and pedagogical practices. This integration is reinforced by transformational leadership, curriculum alignment with global competencies, and the application of project-based learning supported by digital technologies. Despite constraints related to technological infrastructure, the institution demonstrates adaptive capacity in contextualizing and internalizing global entrepreneurial values. The study concludes that the integration of global entrepreneurial values significantly strengthens managerial effectiveness, fosters an innovation-oriented organizational culture, and enhances the global competitiveness of Islamic educational institutions in responding to the complexities of the contemporary global economy.